The answer is above but I don't know if it's correct.
Answer:
We're a different species.
Explanation:
Merry Christmas!
1.7 Btu
1 watt = 3.41214 Btu/h
1watt * 1h = 3.41214 Btu/h * h
1 = 3.41214 Btu/ (watt*h)/
0.5 watt * h = 0.5 watt*h * 3.41214 Btu/(watt*h) = 1.706 Btu
Answer:
k1 + k2
Explanation:
Spring 1 has spring constant k1
Spring 2 has spring constant k2
After being applied by the same force, it is clearly mentioned that spring are extended by the same amount i.e. extension of spring 1 is equal to extension of spring 2.
x1 = x2
Since the force exerted to each spring might be different, let's assume F1 for spring 1 and F2 for spring 2. Hence the equations of spring constant for both springs are
k1 = F1/x -> F1 =k1*x
k2 = F2/x -> F2 =k2*x
While F = F1 + F2
Substitute equation of F1 and F2 into the equation of sum of forces
F = F1 + F2
F = k1*x + k2*x
= x(k1 + k2)
Note that this is applicable because both spring have the same extension of x (I repeat, EXTENTION, not length of the spring)
Considering the general equation of spring forces (Hooke's Law) F = kx,
The effective spring constant for the system is k1 + k2